2012
DOI: 10.1002/pd.2935
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Ebstein's anomaly: early and late appearance

Abstract: Fetal Ebstein's anomaly may be detected in early pregnancy. The incidence is higher than what is reported in newborns. Depiction of a normal fetal heart in early and midpregnancy does not exclude the possibility of subsequent development of Ebstein's anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…In our experience, 99% of fetal cardiac anomalies, with the exception of PS and leiomyoma of myocardium, are detectable by the early mid-trimester screen at 14-17 weeks, and over 90% of them are detected in the low-risk population. In previous studies, we detected almost all of the severe fetal cardiac malformations (hundreds of such cases) in the early second trimester 12,14,15 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In our experience, 99% of fetal cardiac anomalies, with the exception of PS and leiomyoma of myocardium, are detectable by the early mid-trimester screen at 14-17 weeks, and over 90% of them are detected in the low-risk population. In previous studies, we detected almost all of the severe fetal cardiac malformations (hundreds of such cases) in the early second trimester 12,14,15 .…”
Section: Discussionmentioning
confidence: 80%
“…Although PS is relatively common, prenatal diagnosis of this congenital heart defect has been reported only rarely. In these cases, a distinction was made between the finding of pure PS and the more severe finding of pulmonary atresia with an intact ventricular septum. Most cases were described in fetuses beyond the age of 17 weeks; with the exception of our previous report of 11 cases from our current cohort, there have been no publications on the early prenatal diagnosis of PS.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, worse prognosis is observed when EA is combined with other diseases, consistent with the conclusions in our study. Other studies also reported that factors, including fetal edema, cardiac hypertrophy, out ow obstruction, and cardiothoracic ratio > 0.55, are suggestive of poor prognosis for the fetuses 13 . Upon longer duration of TV malformation, the disease will be getting severe gradually; the right heart will be overloaded, thus inducing right heart failure, and increasing the burden of the right heart.…”
Section: Discussionmentioning
confidence: 94%
“…Ebstein's anomaly is a rare cardiac defect of the tricuspid valve, resulting in a range of clinical features depending on the extent of valve displacement, occurring in 1/6000 pregnancies . The tricuspid valve leaflets and chordae are formed from the interior of the right ventricular myocardium by a process called delamination.…”
Section: Introductionmentioning
confidence: 99%